2008
DOI: 10.1016/j.ab.2007.12.023
|View full text |Cite
|
Sign up to set email alerts
|

A solid-phase Bcr-Abl kinase assay in 96-well hydrogel plates

Abstract: Regulated phosphorylation by protein tyrosine kinases (PTKs) such as c-Abl, is critical to cellular homeostasis. In turn, once deregulated as in the Chronic Myeloid Leukemia (CML) fusion protein Bcr-Abl, PTKs can promote cancer onset and progression. The dramatic success of the Bcr-Abl inhibitor imatinib as therapy for CML has inspired interest in other PTKs as targets for cancer drug discovery. Here we report a novel PTK activity and inhibition screening method using hydrogelimmobilized peptide substrates. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…The Z factor considers both dynamic range and variability across multiple samples, with a value of 1 representing a theoretical perfect assay and values over 0.5 being suitable for high-throughput screens. In prior work using either purified c-Abl or Bcr-Abl in bulk K562 lysates, 8 we attained Z factors between 0.5 and 0.9 for the solid-phase kinase assay. In our present study, we were able to obtain a Z factor of 0.4, most likely due to well-to-well variations in the protein concentrations.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The Z factor considers both dynamic range and variability across multiple samples, with a value of 1 representing a theoretical perfect assay and values over 0.5 being suitable for high-throughput screens. In prior work using either purified c-Abl or Bcr-Abl in bulk K562 lysates, 8 we attained Z factors between 0.5 and 0.9 for the solid-phase kinase assay. In our present study, we were able to obtain a Z factor of 0.4, most likely due to well-to-well variations in the protein concentrations.…”
Section: Resultsmentioning
confidence: 79%
“…8 It provides a simple and robust platform to screen small molecules for inhibition of Bcr-Abl in vitro. To accelerate the examination of Bcr-Abl inhibition in cells, we developed a protocol to treat K562 cells in 96-well filter-bottom plates with various small-molecule inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The captured peptide was then incubated with an anti-phosphotyrosine primary antibody (4G10) followed by a horseradish peroxidase-conjugated secondary antibody. Chemifluorescent detection was accomplished by incubating each well with Amplex Red™ reagent and hydrogen peroxide, which gives a fluorescence signal readout that is proportional to the amount of horseradish peroxidase-conjugated antibody in each well, and thus reports the degree of phosphotyrosine present (via the anti-phosphotyrosine antibody) (as described by Wu et al 19 ). Relative fluorescence units (RFU) were measured, which provided a proportional representation of the amount of phosphorylated biosensor present.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a solid-phase PKI screening method in multiwell plates was suggested using an imatinib analog (42). Displacement studies reported in the article demonstrate one of the potential routes to the in vitro application of the radiolabeled SKI230.…”
Section: Discussionmentioning
confidence: 99%